The effect of project-based e-modules on fifth-grade students’ critical thinking in magnetic force and motion - Henny Pusporini; Surayanah Surayanah; I Wayan Dasna (Jurnal Bidang Pendidikan Dasar, 2026)
This study used a quantitative quasi-experimental design with a nonequivalent control group involving 56 fifth-grade students from two public elementary schools in Blitar Regency, Indonesia. The experimental group (n = 28) learned through a Project-Based Learning (PjBL)-based e-module developed with the Heyzine Flipbook platform, while the control group (n = 28) used government textbooks. Cluster sampling selected intact classes. The intervention lasted eight meetings on magnetic force and motion. Pre- and post-tests measured critical thinking skills. The e-module followed six PjBL stages and integrated multimedia elements (animations, videos, simulations, quizzes). Instruments included a critical thinking test, a 25-item motivation questionnaire, and observation sheets. All instruments were expert-validated with strong reliability (Cronbach’s α > 0.80). Data were analyzed using descriptive statistics, independent samples t-test, and two-way ANOVA at a 0.05 significance level.